O efeito protetor do exercício físico e da suplementação com cafeína nas convulsões e dano oxidativo induzido por pentilenotetrazol em ratos - Souza, Mauren Assis de (2012)
Seizures are the main clinical manifestation of epilepsy. Epilepsy is a common neurological disorder with an incidence of 1% in the general population, with about 20 to 30% of patients are refractory to treatment with antiepileptic drugs available. There is evidence for the involvement of reactive oxygen species (ROS) in the pathophysiology of epilepsy, however, determines their role is difficult since oxidative stress can be a cause or consequence of epileptic seizures. Considering the large number of patients refractory to available treatment, and that oxidative damage appears to be an important factor involved in crises, alternative therapies that enhance antioxidant defenses and / or decrease the oxidative damage may become important adjuvants in the treatment of epileptic seizures, as exercise and caffeine administration. In this sense the present work aimed to investigate the effects of physical activity and caffeine supplementation on behavioral and electroencephalographic (EEG) seizures, as well as on changes in oxidative parameters induced by pentylenetetrazol (PTZ) in rats. The first study showed that physical exercise (swimming for 6 weeks) attenuated the onset and duration of generalized seizures induced by administration of PTZ (45 mg / kg i.p) and attenuated the increase in amplitude of EEG waves induced by PTZ (30, 45 and 60 mg / kg i.p). The Pearson correlation analysis revealed that the protection of physical training against seizures, correlates with the content of non-protein thiol (NPT), Na+,K+-ATPase activity and glutamate uptake. Exercise increased the activity of superoxide dismutase (SOD) and the content of the NPT per se. Moreover, physical exercise protect against PTZ-induced neutoxicity, characterized here by ROS production, lipid peroxidation (LPO), protein carbonylation, decreased the content of TNP inhibition of SOD and catalase (CAT) and inhibition of glutamate uptake. The second study, showed that prolonged administration of caffeine (6 mg / kg, 15 days po), but not acute administration decreased the duration of generalized tonic-clonic seizures and attenuated the increase in EEG amplitude induced by PTZ (60 mg / kg i.p). Moreover, prolonged administration of caffeine increased content of reduced glutathione (GSH) per se and protected against increased LPO, ROS and the inhibition of Na+,K+-ATPase activity induced by PTZ. Infusion of L-buthioninesulfoximine (BSO, 3.2 micromol / site, i.c.v), an inhibitor of GSH synthesis, two days before the injection of PTZ, reversed the anticonvulsant effect of caffeine on seizures and oxidative damage induced by PTZ. In addition, a subsequent study has revealed that the prolonged administration of caffeine along with exercise for 4 weeks increased the latency to first myoclonic seizure and first generalized beyond decreased the time spend on generalized seizures induced by the administration of PTZ (60 mg / kg i.p ). Considering the data presented in this study, conclude that physical exercise and supplementation with caffeine attenuates seizures by positively modulating the antioxidant system and maintain Na+,K+-ATPase activity.